From Indicators to Policies: Open Sustainability Assessment in the Water and Sanitation Sector - Iribarnegaray, Martín Alejandro (2015)
A water and sanitation sustainability index (WASSI) was developed and estimated in four cities of the province of Salta, in northern Argentina. The index was built with nine descriptors and fifteen indicators that covered all essential aspects of the sustainability of local water and sanitation management systems. Only one of the cities studied obtained a sustainability value above the acceptability threshold adopted (50 of 100 points). Results indicate that the water company needs to address some environmental and social issues to enhance the sustainability of the systems studied. The WASSI was conceptually robust and operationally simple, and could be easily adapted to the case studies. The index can be followed and updated online on a web site specially developed for this project. This website could be useful to promote participatory processes, assist decision makers, and facilitate academic research. According to local stakeholders, a more open sustainability assessment based on sustainability indices and supported by virtual tools would be relevant and highly feasible. It would help decision makers improve the sustainability and transparency of water and sanitation management systems, and promote more sustainable water policies in the region and beyond.